Appropriateness, transparency, and timeliness in reporting of risk-return in islamic deposits: an exploratory study on mudarabah deposits - Ameer, Rashid; Othman, Radiah; Mahzan, Nurmazilah (2012)
This report finds that given the voluntary nature of the BNM guidelines, these guidelines are not adopted by all the Islamic banks in Malaysia. Furthermore, these guidelines are not stringent because these do not attract any severe penalties for non-compliance in particular with reference to PSIA. We argue that it might be a sign of ineffective corporate governance in Islamic banks. BNM officials seem to take this position that given the growing nature of the Islamic banking sector in Malaysia, it is a very difficult to propose a comprehensive guideline. Even if such a guideline is developed, it will constitute "micro-management" which may not be liked by the Islamic banks and it ensue "tick-boxing" rather than actual compliance. The report also contains a survey of full-fledged Islamic banks in Malaysia. This survey was carried out to determine whether the current disclosure of Islamic banks' relating to investment management, risk and reward faced by Mudarabah (PSIAs) in their annual reports is similar to the new guidelines proposed by research team. The research team incorporated 3 themes: appropriateness, transparency and timeliness into these guidelines which were not addressed in BNM PSIA guidelines. These new guidelines constitute original contribution. The survey findings show that most of the disclosure items proposed in our guidelines were not disclosed in the annual reports of the sample banks. Some of the disclosure items were either being recorded for internal reporting purposes, while others were neither recorded nor reported because these Islamic banks did not feel the need to disclose such items now and in future.